PENGEMBANGAN POTENSI EKONOMI DESA: (Study Pada Desa Larike, Kecamatam Leihitu Barat, Kabupaten Maluku Tengah) - Pesireron, Semy; Situmeang, Mis Fertyno; Patty, Jancen Roland (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2022)
The potential of Larike Village vary such as agriculture and plantation, tourism object and home craft industry. However, these potentials have not been explored in such a way, so it brings profit and even improves the community's economy. This study aims to identify and develope the economic potential of the Larike Village, west Leihitu sub-district, of Central Maluku District. The type of this research is descriptive qualitative. Qualitative approach because this is a case study where the researcher collects a number of indepth information or data on cases symptons related to the economic potential of the village, the Larike Village.  The data analysis used in this study is a Qualitative Descriptive Analysis.  This analysis is focused on identifying the potential sector of the economic village with the  following steps: first, describe economic potential of the village; second: describe the pattern of developing on the  village's economic potential. The result if this study indicates that the agricultural and the plantation sectors can be developed by incraesing the knowledge and skills of farmers. Through agricultural extensions, provision of production support equipment and the formation of farming business groups.  From the tourism object sector can be developed through two approaches namely, the market and physical approaches. From the houshold creative industry sector, it can be developed on aspects of capital and raw materials; and aspects of appropriate technology and marketing.. Key Words: Village’s Economic Potential